2021
DOI: 10.35848/1347-4065/abde54
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of characteristics of thin-film transistor with In2O3 and carbon-doped In2O3 channels by atomic layer deposition and post-metallization annealing in O3

Abstract: Characteristics of thin-film transistors (TFTs) with amorphous In2O3 (InO1.2) and carbon-doped In2O3 (InO1.16C0.04) channels by post-metallization annealing (PMA) process were investigated. The InO1.2 TFT changed from metallic to switching behavior after PMA at 200 °C. In contrast, the InO1.16C0.04 TFT exhibited superior properties such as a threshold voltage (V th) of 3.2 V and a high mobility of 20.4 cm2 V−1 s−1 at PMA 150 °C because of the reduction of excess oxygen vacancies. A large nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
7
2
Order By: Relevance
“…5nm InOx was grown by ALD at 200℃ and patterned. O3 anneal was applied at 200℃ to reduce oxygen vacancy [20]. S/D metal contacts were formed with 20nm TiN.…”
Section: Device Fabricationmentioning
confidence: 99%
“…5nm InOx was grown by ALD at 200℃ and patterned. O3 anneal was applied at 200℃ to reduce oxygen vacancy [20]. S/D metal contacts were formed with 20nm TiN.…”
Section: Device Fabricationmentioning
confidence: 99%
“…In this later method, the variation of the deposition temperature can affect the decomposition and reaction of precursors and lead to changes in the film’s properties, including its conductivity, band gap, or structural characteristics. More recently, it has been reported that low-temperature deposited In 2 O 3 films grown by an ALD method showed the presence of impurities, which mainly consisted of carbon . This residual carbon was expected to mitigate the V O 2 + issues, especially observed at 200 °C deposition temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…μ FE values of 32, 30, and 17 cm 2 V −1 s −1 were reported for the TFTs with a-InO x :Ti, W, and Si channels, respectively [ 13 ]. An atomic layer deposition (ALD) method is also used to form a- or poly-InO x channels for TFTs [ 15 , 16 , 17 , 18 ]. The TFT with a 5 nm thick ALD-deposited carbon-doped a-InO x channel with μ FE of 20.4 cm 2 V −1 s −1 has been demonstrated [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…An atomic layer deposition (ALD) method is also used to form a- or poly-InO x channels for TFTs [ 15 , 16 , 17 , 18 ]. The TFT with a 5 nm thick ALD-deposited carbon-doped a-InO x channel with μ FE of 20.4 cm 2 V −1 s −1 has been demonstrated [ 18 ]. Higher μ FE values of 39.2 and 41.8 cm 2 V −1 s −1 were reported for the TFTs with ultrathin (5 nm) poly-InO x channels formed by plasma- or ozone-assisted ALD followed by postdeposition annealing (PDA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation